(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This study evaluates the relative controls of human induced land-coverchange and natural factors on the chemical status of soils, stream waters, andsediments, mainly through a spatial sampling design. Soils of primary forestswere found to be chemically similar to those of regenerated forests andagricultural land-covers (pastures and coffee plantations), and differences inchemical concentrations between streams draining areas to varying degreescovered by forest were assigned to natural variability. The farmers, however,perceived an overall increase in environmental degradation as well as a changetowards drier and warmer climatic conditions. The climate change was reportedto be the main factor responsible for a negative trend in life quality (rurallivelihoods). The results may be used in the work of identifying priorities andkey factors necessary for environmental and socioeconomic sustainability inIndia. It is suggested that a holistic approach for valuation of forests isessential while examining the issue of compensation for expansion andmaintenance of forest cover. There is need to identify the set of people/institutionsthat bear the cost vis-à-vis the beneficiaries in order to develop anappropriate incentive mechanism. Here, the involvement of local people is ofparamount importance.